Combined Effects of Blue and Ultraviolet Lights on the Accumulation of Flavonoids in Tartary Buckwheat Sprouts - Ji Hongbin; Tang Wen; Zhou Xiaoli; Wu Ying (Polish Journal of Food and Nutrition Sciences)
The effects of blue and UV-A (365 nm)/UV-C (254 nm) or their combinations on the levels of total flavonoids, rutin, quercetin, phenylalanine ammonialyase (PAL), chalcone isomerase (CHI), rutin degrading enzymes (RDEs) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity in tartary buckwheat sprouts were investigated in this study. The total flavonoids content in the tartary buckwheat sprouts irradiated with blue light followed by UV-C (BL+UV-C) raised by 10%, compared with the opposite combination sequence (UV-C+BL). However, blue light did not show the same results when combined with UV-A, and their combinations on the accumulation of total flavonoids were still lower than that of UV-A/UV-C. Key enzymes (PAL, CHI and RDEs) revealed a significant correlation with total flavonoids in tartary buckwheat sprouts.